Found Polaroids (2011- on-going) - Zeleny, Kyler (eTopia, 2017)
The Found Polaroids project started in 2011 with the finding of 484 images and has grown into a personal archival collection of over six thousand Polaroids. e concept behind the project is to breathe new life into long-forgotten images by asking creative minds to write stories about them. e project simply asks for 250-350 word flash-fiction submissions; not of who these people are, but who they could have been. e project has since become a hub of collaboration between photographers, writers and academics advocating for the cultural importance of material photography and found photography. Much of this exchange and collaboration has come about through digital pathways and is part of the material turn facilitated by online exchanges. What makes this collection unique is that most shots are entirely candid and were captured by someone who had a personal relationship with the subjects in the picture. In that sense, each comes coupled with a story that can really only be told by those in front of or behind the camera—but these stories have been lost. Initially, I was fixated on knowing the true stories, but slowly it dawned on me that the importance of stories is not always in their literal truth, but rather in the truth that is reflected in our own lives within these stories. A really great story is simply one that holds a mirror up to our own reality.